The physiological, biochemical and quality of life changes in chronic diabetic foot ulcer after hyperbaric oxygen therapy - Mohd Yazid Bajuri,; Ayesyah A,; Nurhanani Ab,; Mohd Rohaizat Hassan, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Hyperbaric oxygen therapy (HBOT) was established to increase oxygenation and antimicrobial effect that potentially improve the healing of chronic ulcer. Present study aim to assess the effects of HBOT in chronic diabetic foot ulcer (DFU). A total of sixty patients classified according to Wagner 1, 2 or 3 chronic diabetic foot ulcers, were recruited and subsequently divided randomly into two groups; HBOT and control group. All patients underwent the standard treatment for DFU, but for the HBOT group, underwent 20 HBOT sessions, each lasted 80 – 90 mins at 2.5 atmospheres absolute (ATA). White cell count (WCC) and C-reactive protein (CRP) levels were taken during inclusion, at second and fourth week of treatment. Wound sizes were documented at each follow up until six months follow up. SF-36 at one-month post hyperbaric oxygen therapy was used to measure the health-related quality of life. Reduction of WCC and CRP in HBOT group were significant throughout the treatment (p=0.046 and p=0.039, respectively). A total of 26 patients (86.7%) from the HBOT group achieved complete ulcer healing at six months’ follow-up, while 18 patients (60%) in the control group’s ulcer healed completely. Patients treated with HBOT had significantly better mental and physical health constituent of quality of life. It must be emphasised that HBOT is an adjunctive therapy to the standard management of chronic DFU in accelerating wound healing for a better quality of life.